Palladium-catalyzed synthesis and anti-AD biological activity evaluation of N-aryl-debenzeyldonepezil analogues - Jing-Jing Xu; Jiao Luo; Heng Xi; Jin-Bu Xu; Lin-Xi Wan (Frontiers in Chemistry, 2023)
A series of novel N-aryl-debenzeyldonepezil derivatives (1–26) were designed and synthesized as cholinesterase inhibitors by the modification of anti-Alzheimer’s disease drug donepezil, using Palladium catalyzed Buchwald-Hartwig cross-coupling reaction as a key chemical synthesis strategy. In vitro cholinesterase inhibition studies demonstrated that the majority of synthesized compounds exhibited high selective inhibition of AChE. Among them, analogue 13 possessing a quinoline functional group showed the most potent AChE inhibition effect and significant neuroprotective effect against H2O2-induced injury in SH-SY5Y cells. Furthermore, Compound 13 did not show significant cytotoxicity on SH-SY5Y. These results suggest that 13 is a potential multifunctional active molecule for treating Alzheimer’s disease.